Yoruba-Igbo Rivalry 1937-1970: A Historical Analysis of the Birth of Nigeria's Political Dilemma - Udida Undiyaundeye (Universitas Negeri Makassar, 2021)
The political rivalry between the Yoruba and Igbo ethnic nations revolved around their undisputed leaders-Obafemi Awolowo and Nnamdi Azikiwe. It began with the return from the Gold Coast of Nnamdi Azikiwe. His return engendered an Igbo educational awareness that soon challenged the Yoruba domination of the economic and political life of the country; leaving in its wake the carcass of the once vibrant Nigerian Youth Movement (NYM). The brief thaw manifested in the formation of the National Council of Nigeria and Cameroons (NCNC) evaporated with the death of Herbert Macaulay, the erstwhile president of the party in which Nnamdi Azikiwe was the general secretary, Nnamdi Azikiwe and the NCNC did not take kindly to the formation by Obafemi Awolowo and his colleagues of the Edge Omo Oduduwa and subsequently the Action Group (AG). If anything, the general elections of 1951/52 into the Central Legislature exacerbated the rivalry rendering impossible hopes of Coalition governments by the NCNC and AG after the federal elections of 1959 and 1964; and in the process allowed the Northern People’s Congress (NPC) to dictate the direction, pace, and character of Nigeria’s political development, a trend that not even the military interventions and the civil war were unable to alter. This paper attempts to deepen our understanding of this rivalry and concludes that & worked to the utter disadvantage of the two ethnic nations and the Nigerian nation-state.